2020
DOI: 10.1186/s12893-020-0675-5
|View full text |Cite
|
Sign up to set email alerts
|

Identifying risk factors for metastasis to the level VII lymph node in papillary thyroid carcinoma patients

Abstract: Background: The level VI lymph nodes are anatomically connected to the level VII lymph nodes and papillary thyroid carcinoma (PTC) can metastasis to both regions. The aim of this study was to identify clinicopathologic factors associated with level VII lymph node metastasis. Methods: Between March 2015 and September 2016, a total of 275 consecutive patients were operated on for PTC with prophylactic level VII dissection at the Sir Run Run . Patients with PTC were performed via video-assisted approach. Multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…On the other hand, there are studies reporting that the risk increases in tumors located in the middle and/or lower part of the thyroid lobe. 28,29 It was also reported that the risk of metastasis increased in tumors in the isthmus, inferior anterior-central, inferior posterior-lateral, and middle posterior-lateral regions. 30 It is clear that the results of studies examining the relationship between the intrathyroidal tumor localization and central compartment metastasis do not agree with each other.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, there are studies reporting that the risk increases in tumors located in the middle and/or lower part of the thyroid lobe. 28,29 It was also reported that the risk of metastasis increased in tumors in the isthmus, inferior anterior-central, inferior posterior-lateral, and middle posterior-lateral regions. 30 It is clear that the results of studies examining the relationship between the intrathyroidal tumor localization and central compartment metastasis do not agree with each other.…”
Section: Discussionmentioning
confidence: 96%
“… 11 Other researchers have reported that when thyroid cancer invades the upper mediastinal vessels or leads to obvious upper mediastinal lymph node metastasis, endoscopic-assisted mediastinal lymph node dissection can be attempted. 5 …”
Section: Discussionmentioning
confidence: 99%
“…11 Other researchers have reported that when thyroid cancer invades the upper mediastinal vessels or leads to obvious upper mediastinal lymph node metastasis, endoscopicassisted mediastinal lymph node dissection can be attempted. 5 Many studies to date have indicated that three-port thoracoscopy under the xiphoid process has outstanding advantages in the treatment of thymic tumors and other upper mediastinal tumors and even in the performance of upper mediastinal lymph node dissection. With the favorable magnification and lighting functions of the endoscope, the tumors can be removed more thoroughly and with less trauma, more rapid recovery, and a more reliable effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation